Analisis Fraud Triangle terhadap Indikasi Korupsi pada Ketua Ombudsman Republik Indonesia sebagai Pimpinan Lembaga Pengawas Negara Independen - Olivia Lovina Hermanto; Trifena Hanayomi Sutanto; Naila Syifa Azahra; Safira Permata Kristia Putri; Tries Ellia Sandari (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
Corruption committed by the leader of an independent state oversight institution represents a paradox that fundamentally undermines the legitimacy of government governance. This study examines the case of Hery Susanto, Chairman of the Ombudsman of the Republic of Indonesia, who was designated as a corruption suspect by the Attorney General's Office on April 16, 2026—merely six days after his inauguration—in connection with alleged bribery of Rp1.5 billion from PT Toshida Sulawesi Hijau Indonesia involving the management of Non-Tax State Revenue (PNBP) in the nickel mining sector for the period 2013–2025. This study aims to analyze the manifestation of the three elements of the Fraud Triangle—pressure, opportunity, and rationalization—within this case, and to formulate systemic implications for corruption prevention in independent state institutions. Employing a normative-empirical legal research approach with a case study method, data were collected through documentation and qualitative content analysis of legal documents, official press releases from the Attorney General's Office, and verified media reports. The findings reveal that pressure stemmed from financial motivation and career ambition; opportunity arose from weak internal oversight mechanisms, the perpetrator's strategic position, and regulatory gaps in Law Number 37 of 2008; while rationalization manifested through cognitive justification that framed the receipt of compensation as a reasonable reward for services rendered. This study contributes to the literature on forensic accounting and corruption criminology, while recommending the establishment of an independent Ombudsman Supervisory Board and the strengthening of a digital-based early detection system.